Development of a successful microfinancing system : actor-network theory perspective - Waniak-Michalak, Halina (Array, 2019)
The article aims to answer the following research question: “How were actors mobilized to form a network for promoting microfinancing system in a transforming country?”. For this case study, we employ the actor-network theory (ANT) as a lens and interpretation tool. We used the focus research, in-depth interviews, and analysis of documents as sources in our study. The article shows how the different purposes of each actor can affect or hinder the achievement of benefits for all actors. We pointed to the goals and problems they had to solve, as to create a network to reach the primary goal which was the creation of a sustainable market economy in Poland. The focal actors (government, SMEs, banks, NGOs) had to create the microfinancing network, which works quite successfully. It enables access to capital to entrepreneurs who would not get it from banks. However, unethical acts, committed by some actors may cause the system to collapse or change in the future, as actors will adopt different goals and new actors will join in. A change in the method of the guarantee funds’ financing, limitation of EU financial resources, changing needs of entrepreneurs, further transformations of the Polish banking system - all these events may result in the creation of a new network of connections and a new system.